Coquetelaria e turismo criativo: uma proposta pedagógico-reflexiva em curso de tecnologia em gastronomia - Pujol, Edemilson Rosa (My University, 2020)
Taking into account the General National Curriculum Guidelines for the organization and functioning of the Technology Higher Education Courses and the National Catalog of Technology Higher Education Courses (2016), this project aims to propose a unit study plan of the Cocktail discipline (this is, as a rule, part of the curricular structure of a Technology Course in Gastronomy), whose didacticpedagogical process, theoretically and methodologically based on meaningful learning, aims to promote: (a) the articulation of knowledge related to cocktail and the drinks involved there with other areas of knowledge, contextualizing and deepening this knowledge relationally; (b) the passage from a know-how restricted to the technical domain, to a reflexive theoretical-practical doing; (c) the conception and design of a situational context linked to Creative Tourism to which the selected contents are directed and the proposition of learning activities. These objectives highlight the prospect of going beyond a teaching plan proposition linked only to techniques and cocktail recipe development. The intention is to stimulate reflexive processes in order to contribute to the development of meaningful learning in the area, encompassing corresponding cognitive, affective and emotional processes.
Tendo em conta as Diretrizes Curriculares Nacionais Gerais para a organização e o funcionamento dos cursos superiores de Tecnologia e do Catálogo Nacional de Cursos Superiores de Tecnologia (2016), o presente projeto tem como objetivo a proposição de um plano de estudos de unidade da disciplina Coquetelaria (esta, via de regra, integrante da estrutura curricular de um curso de Tecnologia em Gastronomia), cujo processo didático-pedagógico, teórica e metodologicamente fundamentado na aprendizagem significativa, volta-se a promover: (a) a articulação de conhecimentos referentes à Coquetelaria e às bebidas aí implicadas com outras áreas do conhecimento, contextualizando e aprofundando esses saberes de forma relacional; (b) a passagem de um saber-fazer restrito ao domínio técnico, para um fazer reflexivo teórico-prático; (c) a concepção e o desenho de um contexto situacional atrelado ao Turismo Criativo para o qual se voltem os conteúdos selecionados e a proposição das atividades de aprendizagem. Nesses objetivos, evidencia-se a perspectiva de ir além de uma proposição de plano de ensino vinculado apenas a técnicas e ao desenvolvimento de receitas de coquetéis. Tem-se o intento de estimular processos reflexivos, com vistas a contribuir para o desenvolvimento de aprendizagens significativas na área, abarcando processos cognitivos, afetivos e emocionais correspondentes.
Keywords: Turismo; Gastronomia - Estudo e ensino; Aprendizagem; Coquetéis; Tourism; Gastronomy - Study and teaching; Learning; Cocktails